Cross-Border Mergers & Acquisitions Policy in Service Markets - Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2008)
We provide facts showing that in service markets: (i) restrictions on foreign direct investment (FDI) are under reform, (ii) cross-border Mergers & Acquisitions dominate as the entry mode of FDI, and (iii) there is often a high market concentration. Based on these facts, we present a model for analyzing cross-border M&A policy in liberalized service markets taking into account efficiency and market power effects. Our findings suggest that a merger policy, but not a discriminatory policy towards foreigners, seems warranted. Moreover, policies ensuring competition for domestic target firms seem warranted. In this vein, harmonization of the EU takeover regulations may particularly benefit assets owners in countries with many target firms.
Keywords: F23; K21; L13; O12; 330; Services; Mergers and Acquisitions; Investment Liberalization; Foreign Direct Investments; Ownership; Fusion; Übernahme; Multinationales Unternehmen; Dienstleistungssektor; Theorie; OECD-Staaten